Bones of the Sun God - Vegas, Peter, 1968- (Vegas, Peter, 1968- Pyramid hunters, 2018)
Having returned from his adventures in Egypt, Sam Force is itching to get out of his boarding school once again in order to find his long-lost parents, who he has learned are not actually dead. However, his uncle Jasper has forbidden him from leaving until he can go with him. When someone from his Egypt adventure shows up on his doorstep though, Sam knows he can't wait to go to Belize on the next quest. Thankfully, his friend Mary Verulam has a plan.